PENGARUH POSISI CENTERBULB BERBENTUK FOIL TERHADAP KOMPONEN HAMBATAN KAPAL IKAN KATAMARAN MV. LAGANBAR - Muhammad Iqbal; Parlindungan Manik; Eko Sasmito Hadi; Achmad Kurniawan (Politeknik Negeri Batam, 2020)
Catamarans are double hull ships which have many advantages over single hull ships with the same displacement. To increase catches, fishermen in Cilacap converted ships from the original single hull with outrigger to double hull (catamaran). Displacement of ships has doubled. But the ship's resistance increased to almost 4 times. To reduce the resistance of catamarans, some researchers use the concept of center bulb. In this study, the center bulb form used foil. The purpose of this study was to determine the effect of center bulb position on ship resistance components by comparing 9 center bulb positions. The results stated that of the nine center bulb position configurations, Model 6 is the best model because at Fr 0.35 it can reduce ship resistance by up to 33%. For the viscous resistance component it is not significantly affected by the use of the center bulb. But on the wave resistance component, the use of this center bulb can reduce wave resistance by 47% at Fr 0.35.